2018
DOI: 10.22146/jmpf.34441
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Pharmacist and Influencing Factors in the Era of National Healt Insurance at Puskesmas

Abstract: ABSTRAKPuskesmas merupakan salah satu fasilitas kesehatan tingkat pertama yang menyelenggarakan Jaminan Kesehatan Nasional. Apoteker sebagai penanggung jawab kefarmasian di Puskesmas wajib mengikuti Standar Pelayanan Kefarmasian di Puskesmas yang tercantum dalam Peraturan Menteri Kesehatan (PMK) No. 74 Tahun 2016 untuk menjamin keselamatan pasien, namun dalam implementasinya pelayanan kefarmasian di Puskesmas belum dilakukan sesuai standar sehingga analisis kinerja apoteker perlu dilakukan. Tujuan penelitian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
1
2
0
2
Order By: Relevance
“…In this study, regarding drug administrators at the puskesmas, the pharmacist group was in accordance with the research conducted by Satibi and the authors (2018) that showed that the majority of pharmacists in the puskesmas were women (Satibi et al, 2018). On the other hand, the non-pharmacist drug administrators were in accordance with research conducted by Athijah and the authors ( 2018), which presented that the majority of drug administrators were women (60%) (Athijah, Rahem & Setiawan, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…In this study, regarding drug administrators at the puskesmas, the pharmacist group was in accordance with the research conducted by Satibi and the authors (2018) that showed that the majority of pharmacists in the puskesmas were women (Satibi et al, 2018). On the other hand, the non-pharmacist drug administrators were in accordance with research conducted by Athijah and the authors ( 2018), which presented that the majority of drug administrators were women (60%) (Athijah, Rahem & Setiawan, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…The results of this study were in accordance with the characteristics of pharmacists in Indonesia, as seen in other research conducted by Satibi and the authors (2018) in different practice settings. For example, at the Health Center (Puskesmas) in 2018, the majority of pharmacists were women (72.2%) (Satibi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Berdasarkan penelitian Ismail (2020), diketahui bahwa faktor yang dapat menyebabkan tingginya jumlah tenaga kefarmasian berjenis kelamin perempuan di antaranya adalah pada proses perkuliahan dan pada saat pekerjaan kefarmasian diperlukan tingkat ketelitian yang tinggi, yang masyarakat berasumsi bahwa orang dengan jenis kelamin perempuan memiliki tingkat ketelitian yang tinggi dibandingkan orang dengan jenis kelamin laki-laki, dan berdasarkan faktor biologi yang dimiliki perempuan, terdapat hormon estrogen dan progesterone yang membuat perempuan bersifat feminim, yang mana sifat ini dipersepsikan lebih cocok untuk pekerjaan kefarmasian. Hasil ini seperti yang disebutkan dalam penelitian Satibi (2018), yaitu jumlah tenaga kefarmasian yang berjenis kelamin perempuan lebih banyak dibanding tenaga kefarmasian yang berjenis kelamin laki-laki.…”
Section: Karateristik Respondenunclassified